EVALUATION OF THE IMPLEMENTATION OF PSAK 24 REVISION 2015 REGARDING EMPLOYMENT BENEFITS ESPECIALLY POSTEMPLOYMENT AT PT BA BANGUNAN - Purwatiningsih - (JAF (Journal of Accounting and Finance), 2022)
Employee benefits are obligations of every company that has a major influence on the company from an external perspective such as stakeholders in this case the company owner or creditors and internal such as workers who will have a direct impact on the company's performance. Due to its great influence on the company, it is deemed necessary for the purpose of this study to properly disclose in accordance with generally accepted financial accounting standards. This study uses a qualitative descriptive research method. The results of the research at PT BANGUNAN Pondok Cabe, South Tangerang, it can be concluded that the employee benefits at PT BA BANGUNAN can be categorized into three categories based on PSAK 24, namely short-term employee benefits, post-employment benefits, and severance pay. PSAK 24. Company management should remain consistent in the application of PSAK 24 so that information on employee benefits reporting remains reliable.